2016
DOI: 10.1097/01.aoa.0000489471.91909.66
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Secondary Postpartum Hemorrhages: A Historical Cohort Study

Abstract: (Birth. 2015;42(3):235–241) Immediate postpartum hemorrhage is a common and dangerous complication for which risk factors have been established. However, there is a distinct lack of research regarding secondary postpartum hemorrhage, with only 2 studies reporting on possible risk factors. These studies found a variety of risk factors, including immediate postpartum hemorrhage, hemorrhage during pregnancy, manual removal of the placenta, a history of secondary postpartum hemorrhage, hospitalization du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…As in our study, frequency of secondary postpartum hemorrhage in women was observed in 20 Asian countries reported prevalence of secondary postpartum hemorrhage ranging from 11% (India) 13 to 39% (Sri Lanka) 14 32% in Nigeria 15 While in developed countries Boyd et al 16 and Iraha Y 17 et al reported 0.2% of deliveries and other studies reported rates ranging from 1% -2%. 18,19 the variation is reported frequency in developing countries could be explained in part as the majority of patients were found to be non-booked, had not received antenatal care and were delivered by un-skilled persons who might not have actively managed the third stage of labour leading to retained placenta and membrane in turn causing sepsis and further aggravating the maternal condition.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…As in our study, frequency of secondary postpartum hemorrhage in women was observed in 20 Asian countries reported prevalence of secondary postpartum hemorrhage ranging from 11% (India) 13 to 39% (Sri Lanka) 14 32% in Nigeria 15 While in developed countries Boyd et al 16 and Iraha Y 17 et al reported 0.2% of deliveries and other studies reported rates ranging from 1% -2%. 18,19 the variation is reported frequency in developing countries could be explained in part as the majority of patients were found to be non-booked, had not received antenatal care and were delivered by un-skilled persons who might not have actively managed the third stage of labour leading to retained placenta and membrane in turn causing sepsis and further aggravating the maternal condition.…”
Section: Discussionsupporting
confidence: 61%
“…While the result of a Nigerian study by Ijaiya MA et al 21 showed mothers suffering from PPH are usually of age 35 years. Multiparity was commonly observed in our study whereas study by Debost A 20 and Ijaiya MA 21 reported majority of grand multiparous women with secondary postpartum haemorrhage.…”
Section: Discussionmentioning
confidence: 45%